UPAYA PENINGKATAN HASIL BELAJAR KIMIA FISIKA 5 DENGAN PENDEKATAN CHEMO-ENTREPRENEURSHIP MELALUI KEGIATAN LESSON STUDY - Kadarwati, Sri; Saputro, Subiyanto Hadi; Priatmoko, Sigit (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2010)
Physical Chemistry 5 is a main and diffi cult course for students because of itsrelation to microsspic properties and abstract with the result that the visualization isnecessity. Therefore, the appealing learning that can manure the studentsÃ¢â¬â¢ creativenessand innovation and motivate students to be entrepreneurs is necessity. Such learning is alearning using chemo-entrepreneurship (CEP) approach. Lesson study activity is potentialin learning community and collaboration development effectively. Therefore, the learning ofPhysical Chemistry 5 using CEP approach through lesson study activity is necessity. Thisresearch was aimed to improve the studentsÃ¢â¬â¢ achievement on Physical Chemistry 5 lectureusing CEP approach through lesson study activity. This research was conducted by quasiexperiment method involving students on seventh semester of Chemistry Programme assubject. Lesson study activity was conducted by three stages i.e. planning, doing, andrefl ecting. The instrument of research included the achievement test, observation sheets,and questionnaire sheets. The results showed that the achievement of experimental groupwas higher than of controlled group. The learning completeness of experimental group washigher than of controlled group. It was shown that this learning can improve studentsÃ¢â¬â¢ life skill.ÃÂ Key words: achievement, chemo-entrepreneurship, lesson study